The green space : the transformation of the Irish image - Casey, Marion R., 1962- (New York : New York University Press, 2024)
"There is more to Irish than St. Patrick's Day and Guinness. The word Irish conjures an array of images, each with a long history. Who defined Irish? In the twentieth century Ireland, the United States, and Irish America were all invested in representation. Exerting or losing control of an ethnic image had ramifications on both sides of the Atlantic"--
List of figures -- List of tables -- Introduction -- Vested interests -- Media matters -- Cultural currency -- Racial reckoning -- Selling value -- Emerald sheen -- Come back to Erin -- Conclusion -- Acknowledgments -- Abbreviations -- Bibliography -- About the author -- Notes
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 25, 2024).
JSTOR
Keywords: National characteristics, Irish; Irish -- Ethnic identity; Irish Americans -- History; Ireland -- History -- 20th century; Irlandais; Irlandais -- Identité ethnique; Irlande -- Histoire -- 20e siècle.; HISTORY / United States / General; Irish Americans; Irish -- Ethnic identity; National characteristics, Irish; Ireland; 1900-1999; History